Amplification mecA Gene and SCCmec MRSA Isolates Isolated From Healthy individuals in NIlai. - Chia, Zheng Yang (2017)
Resistance in methicillin-resistant Staphylococcus aureus and methicillin-resistant Staphylococcus epidermidis is due to the presence of mecA which encodes for penicillin – bidning protein (PBP2a). PBP2a is able to prevent the action of methicillin and enables the bacteria to synthesize peptidoglycan and grow. The mecA gene is found in the staphylococcal cassette chromosome mec (SCCmec ) element. Chuah (2016) isolated possible MRSA and MRSE isolates from healthy individuals in Nilai. This was followed by an attempt by Kum (2017) to amplify the SCCmec elements and the mecA gene of the MRSA and MRSE isolates respectively but was unsuccessful. Thus, the aim of his study was to amplify the SCCmec types in the MRSA isolates by optimizing the PCR reactions. These isolates were cultured and confirmed through Several confirmatory test as well as the antibiotic susceptibility assay using cefoxitin. Based on the zone of inhibition, isolate A/2016M/14 was found to be resistant towards cefoxitin. No MRSE was identified. The DNA of this resistant isolate was extracted using the crude extraction method and subjected to PCR. Isolate A/2016M/14 was confirmed to be MRSA as the mecA gene and the type II SCCmec element were successfully amplified. Since, the mecA gene and the type II SCCmec elements were successfully amplified using the recommended conditions, no optimization of amplification was done. The DNA sequence analysis through BLAST also confirmed that isolate A/2016M/14 was MRSA with type II SCCmec element. The result of BLAST showed that the sequence amplified using KDP primerswas in consensus with DNA sequence encoding for type II SCCmec with 99% similarities. Hence, it can be confirmed that isolate A/2016M/14 is hospital-acquired MRSA as it carries the type II SCCmec. The human carrier of isolate A/2016M/14 could have been treated with antibiotics or could have some in contact with another MRSA carrier or could have contracted it from a clinical setting or from the environment. This carrier could transmit this resisitrant strain to other individuals in INTI International University. Therefore, every individuals should practice good hygiene in order to minimize the risk of infection caused by MRSA.